The case for a primary social drive: Revisiting definitions for primary drives - Morten Christoffersen (Acta Psychologica)
This paper analyzes the social drive, from the shared foundation of behavioral psychology, ethology, and attachment theory. It explores how the social drive has been considered a secondary or acquired drive and identifies the original advocates for this perspective, while outlining their prerequisites for primary drives. This provides a framework for empirical investigation which include 1) having a physiological component, 2) survival value for the species, 3) not relying on pairing with other primary reinforcers, and 4) displaying covariation with behavior based on satiation and deprivation. The paper gradually moves from older studies to modern ones, demonstrating that the social drive fulfills all criteria, by utilizing older empirical studies on isolation, bad rearing, neonatal social reinforceability, as well as modern research on social deprivation/satiation and loneliness. The paper concludes by discussing the implications of this reclassification on existing psychological theories, and its potential to influence future psychotherapeutic treatments.